Corticosteroid Therapy in Neonates Undergoing Cardiopulmonary Bypass: Randomized Controlled Trial - Graham, Eric M; Martin, Reneé H; Buckley, Jason R; Zyblewski, Sinai C; Kavarana, Minoo N; Bradley, Scott M; Alsoufi, Bahaaldin; Mahle, William T; Hassid, Marc; Atz, Andrew M (Journal of the American College of Cardiology, 2019)
The efficacy of intraoperative corticosteroids to improve outcomes following congenital cardiac operations remains controversial. The purpose of this study was to determine whether intraoperative methylprednisolone improves post-operative recovery in neonates undergoing cardiac surgery. Neonates undergoing cardiac surgery with cardiopulmonary bypass at 2 centers were enrolled in a double-blind randomized controlled trial of methylprednisolone (30 mg/kg) or placebo after the induction of anesthesia. The primary outcome was a previously validated morbidity-mortality composite that included any of the following events following surgery before discharge: death, mechanical circulatory support, cardiac arrest, hepatic injury, renal injury, or rising lactate level (>5 mmol/l). Of the 190 subjects enrolled, 176 (n = 81 methylprednisolone, n = 95 placebo) were included in this analysis. A total of 27 (33%) subjects in the methylprednisolone group and 40 (42%) in the placebo group reached the primary study endpoint (odds ratio [OR]: 0.63; 95% confidence interval [CI]: 0.31 to 1.3; p = 0.21). Methylprednisolone was associated with reductions in vasoactive inotropic requirements and in the incidence of the composite endpoint in subjects undergoing palliative operations (OR: 0.38; 95% CI: 0.15 to 0.99; p = 0.048). There was a significant interaction between treatment effect and center. In this analysis, methylprednisolone was protective at 1 center, with an OR: 0.35 (95% CI: 0.15 to 0.84; p = 0.02), and not so at the other center, with OR: 5.13 (95% CI: 0.85 to 30.90; p = 0.07). Intraoperative methylprednisolone failed to show an overall significant benefit on the incidence of the composite primary study endpoint. There was, however, a benefit in patients undergoing palliative procedures and a significant interaction between treatment effect and center, suggesting that there may be center or patient characteristics that make prophylactic methylprednisolone beneficial.